The determinants of ṣukūk issuance in GCC countries - Imene Guermazi (Islamic Economic Studies (IES), 2020)
Purpose - This paper focuses on ṣukūk issuance determinants in Gulf Cooperation Council (GCC) countries. Given the dual characteristic of debt and equity of ṣukūk as well as their unique benefits of social responsibility, the author questions whether the theories of capital structure, the trade-off and the pecking order are able to well explain the ṣukūk issuance. Design/methodology/approach - First, the author verifies these theories using capital structure determinants and regresses the ṣukūk change on these determinants. Second, the author tests the trade-off theory with the target debt model and third, verifies the pecking order theory using the fund flow deficit model. Findings - The empirical results show that capital structure determinants fail to explain both theories. The author confirms that the ṣukūk change is significatively linked to the deviation from a ṣukūk target. So, issuing firms balance the marginal costs of ṣukūk and their benefits of religiosity and social responsibility toward a target debt. The author finds no evidence of the pecking order theory. Research limitations/implications - This study contributes to corporate finance theory and corporate social responsibility. It verifies if capital structure theories proved in conventional financing can well explain Islamic bonds issuance given their social responsibility benefits. Practical implications - Managers and investors would pay attention to the social factors explaining ṣukūk issuance in their finance and investment decisions. They would be enhanced to use this financing tool knowing its social unique benefits. This also should encourage governments to enhance this socially responsible financing. Rating agencies would be motivated to evaluate ṣukūk and firms would improve the quality and relevance of disclosure to get the best rating. Social implications - The author highlights the social factors explaining ṣukūk issuance and enhances corporate social responsibility (CSR). Originality/value - The author extends the few literature testing capital structure theories for Islamic bonds and highlights the specific social responsible features of ṣukūk that would bridge their issuance to capital structure theories. So the author enhances the concept of Islamic CSR. Tying capital structure theories to CSR would also help developing Islamic finance theory as a unique social responsible framework.
Keywords: G11; G12; G32; 330; Pecking order theory; Social responsibility; ṣukūk issuance; Trade off theory